ANALISIS RASIO PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PADA INDUSTRI TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hadriana Hanafie (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The objective of this research is to know and analyze whether profitability ratios in Textile and Garment Industry can be used to assess company's financial performance in Indonesia Stock Exchange. The analytical method used is quantitative descriptive analysis. The results of this study indicate that: the profitability ratios of Textile and Garment Industries listed on the Indonesia Stock Exchange for 3 years ie in 2013 until 2015 is good, which is shown by cost of goods sold and gross profit and income before taxes have increased considerably although still fluctuate every year.